Mahfuzât: Cezayir İbâdîleri Arasında Beş Gün - Mehmet Söylemez (İslami İlimler Dergisi)
UDGD 0DªKHGXªO 0HQKHF DGÈQD éVD éVD NDUëÈODGÈ 6RQ GHUHFH VHYHFHQ HVSLULOL KDILI VDNDOOÈ 0L]DEv \DQL (PD]LèOHUGHQ ELU JHQo RODQ éVD éVD E 6DOLK RQODUGDQ ]L\DGH GDKD oRN $UDSODUD EHQ]HPHNWH\GL 2QXQOD ELUOLNWH NDODFDèÈPÈ] \XUW RODQ %XUFXªO .HIIkQ VHPWLQLQ HO +DOOkW PDKDOOHVLQGH \HU DODQ HO +LNPH LVLPOL 'DUXªW WDOHEHª\H GRèUX \RO DOÈ\RUX] 0XKDPPHG %DEDDPPv KRFD\OD LUWLEDW NXUGXèXPX]GD HQVWLWOHULQGH ELU PLVDILUKDQHOHULQLQ ROGXèXQX GLOHUVHN EX UDGD GLOHUVHN EDëND ELU PHNDQGD YH\D |èUHQFLOHUOH ELUOLNWH NDODELOHFHèLPL]L V|\OHPLëWL %L] |èUHQFLOHUL WDQÈPDN LVWHGLèLPL] LoLQ \XUWWD NDOPD\È WHUFLK HW